Prevalence of substance use among male adolescents in an urban slum area of Karimnagar district, Andhra Pradesh - Prashant R Kokiwar; Gopal Rao S Jogdand (Wolters Kluwer Medknow Publications, 2011)
In recent years substance use has increased greatly throughout the world. Adolescence is the critical period when the first initiation of substance use takes place. Interventions at the adolescent age are effective to bring about lifestyle modifications. A community-based, cross-sectional study was carried out among 260 randomly selected adolescents in an urban slum area, with the objective of studying the prevalence and determinants of substance use among adolescents. The adolescent age group was selected as defined by the World Health Organization (WHO) (10 - 19 years). The overall prevalence of substance use was 32.7%. About 31% initiated substance use at 13 - 15 years of age, and the reason was peer pressure in 52.9%. Education of the study subject, education of parents, and substance use by parents and by peers were significantly associated with substance use. Children and parents should be educated to prevent substance use. There was a need to change the social environment.